Association of Social Networking Systems Use with Mental Health and Well-being: A Cross-sectional Study (Kerala Journal of Psychiatry, 2024)
Background: Social Networking Systems (SNS) are web-based services integral to global communication and social interaction. This study explores predictors of smartphone addiction, the role of motivation and psychosocial well-being, and the prevalence and predictive role of anxiety and depression in smartphone addiction.Materials and Methods: This survey-based study used Google Forms to collect data through a predesigned questionnaire and other standardized scales. It was conducted over five days and shared through various SNS platforms.Results: 78.69% identified themselves as netizens and 38.5% met the criteria for smartphone addiction, which was used as a window to assess SNS use. The psychological well-being scale scores were higher in participants without smartphone addiction. Higher scores in personal growth (p=0.001), environmental mastery (p=0.02), and self-acceptance (p=0.002) were significantly associated with lower smartphone addiction. Personal growth subscale and Behavioural Inhibition System Scores were statistically significant predictors for smartphone addiction. A significant association was found between depression levels and smartphone addiction. Conclusion:  Individuals struggling with psychosocial well-being, low self-acceptance, lack of control over their environment, and inadequate coping skills for personal growth are likely to use SNS as a refuge.  Depression needs to be ruled out while exploring smartphone addiction.Conflict of Interest: NoneSource/s of Research Funds: Self
Keywords: Social Networking System; Depression; Anxiety; ,Psychosocial Well-being; Behavioural Inhibition System